2021
DOI: 10.3390/land10111241
|View full text |Cite
|
Sign up to set email alerts
|

A High–Resolution Accumulation Record of Arsenic and Mercury after the First Industrial Revolution from a Peatland in Zoige, Qinghai–Tibet Plateau

Abstract: The impacts of human activities on Zoige peatlands are poorly documented. We determined the concentrations and accumulation rates of As and Hg in a 210Pb-dated peat profile collected from this area and analyzed the correlations between accumulation rates of both As and Hg and other physicochemical properties. To reconstruct recent conditions of As and Hg, we analyzed peat sediments of Re’er Dam peatland in Zoige using 210Pb and 137Cs dating technologies. The concentrations of total As (86.38 to 174.21 μg kg−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…On the other hand, high concentrations of metals can be toxic to plants and microbes, reducing their abundance and productivity (Glass and (smelters, metal processing). Mercury is a notable exception as some studies have indicated enrichment of Hg in peatlands close to industrial sources (Fitzgerald et al 2018;Chen et al 2021), while other studies indicated Hg enrichment farther away from emission point due to its distinct atmospheric behavior in the gaseous phase (Pearson et al 2019;Floreani et al 2020). Therefore, Hg recorded in peatlands may originate from local or regional sources.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high concentrations of metals can be toxic to plants and microbes, reducing their abundance and productivity (Glass and (smelters, metal processing). Mercury is a notable exception as some studies have indicated enrichment of Hg in peatlands close to industrial sources (Fitzgerald et al 2018;Chen et al 2021), while other studies indicated Hg enrichment farther away from emission point due to its distinct atmospheric behavior in the gaseous phase (Pearson et al 2019;Floreani et al 2020). Therefore, Hg recorded in peatlands may originate from local or regional sources.…”
Section: Introductionmentioning
confidence: 99%
“…However, all the studies about soil in this area have mainly focused on the distribution of soil organic carbon (Tian et al, 2003;Luan et al, 2014;Ma et al, 2016), the characteristics of wetland soil moisture and nutrients (Tian et al, 2005;Gao et al, 2011), wetland degradation (Li et al, 2011;Huo et al, 2013;Hu et al, 2015), and soil microbial community (Niu et al, 2011;Tian et al, 2012;Yun et al, 2012;Wu et al, 2016). Till now, only a little research has concentrated on the heavy metals in soils from the Zoige alpine basin (Chen et al, 2021). For example, the heavy metal contents of the Zoige basin were determined by hyperspectral remote sensing technology (Yuan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%